Pleomorphic adenoma of minor salivary glands of the palate – clinical and histopathological aspects of the tumour - Popowski, Wojciech; Pokrowiecki, Rafał; Kubicka- Pertkiewicz, Małgorzata; Frank, Szymon; Wojtowicz, Andrzej (Journal of Stomatology, 2015)
Pleomorphic adenoma (PA) is the most common benign neoplasm of salivary glands. Although it occurs mostly in major salivary glands, it may also occur in minor salivary glands. Salivary glands of the hard palate are the most common location of minor salivary glands PA. The tumour usually presents as a painless, firm swelling covered with normal mucosa. Development of the tumour takes years. It exhibits wide cytomorphological and cytoarchitectural diversity. The main feature is presence of both epithelial and myoepithelial cells in stroma with variable characteristics. Three types of PA are distinguished: classic (equal qualitative cell to stroma ratio), cell- rich and stroma-rich. Histological composition may influence clinical features of the tumour, such as firmness, elasticity and size. The objective was to present relationship between clinical features of PA and histopathological findings. Assessment included three clinical cases of patients with diagnosed PA of minor palatal salivary glands. In all patients surgical excision of the tumour with normal tissue margin was performed. Two cases presented classic sub-type PA. One case was cell-rich subtype PA. Classic and stroma-rich subtypes of PA grow to bigger sizes than the cell-rich subtype and are more firm and elastic. This is due to the presence of hyaline, cartilage and even bone tissue in the stroma. The cell-rich subtype achieves smaller sizes and is less firm and elastic. Risk of malignant change is found to be higher in the cell- rich subtype. Histological picture has an impact on clinical features of the tumour. Treatment of choice is radical removal of the neoplasm.